A comparative analysis between the effects of galactose and glucose supplementation on endurance performance - Macdermid, P. W.; Stannard, S. R.; Rankin, D.; Shillington, D. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
To determine beneficial effects of short-term galactose (GAL) supplementation over a 50:50 glucose- maltodextrin (GLUC) equivalent on self-paced endurance cycling performance. Methods: On 2 separate occasions, subjects performed a 100-km self-paced time trial (randomized and balanced order). This was interspersed with four 1-km and four 4-km maximal efforts reflecting the physical requirements of racing. Before each trial 38 ± 3 g of GAL or GLUC was ingested in a 6% concentrate fluid form 1 hr preexercise and then during exercise at a rate of 37 ± 3 g/hr. Performance variables were recorded for all 1- and 4-km efforts, all interspersed intervals, and the total 100-km distance. Noninvasive indicators of work intensity (heart rate [HR] and rating of perceived exertion) were also recorded. Results: Times taken to complete the 100-km performance trial were 8,298 ± 502 and 8,509 ± 578 s (p = .132), with mean power outputs of 271 ± 37 and 256 ± 45 W (p = .200), for GAL and GLUC, respectively. Mean HR did not differ (GAL 157 ± 7 and GLUC 157 ± 7 beats/ min, p = .886). A main effect of carbohydrate (CHO) type on time to complete 4-km efforts occurred, with no CHO Type × Effort Order interaction observed. No main effect of CHO type or interaction of CHO Type × Sequential Order occurred for 1-km efforts. Conclusion: A 6% GAL drink does not enhance performance time during a self-paced cycling performance trial in highly trained endurance cyclists compared with a formula typically used by endurance athletes but may improve the ability to produce intermediate self-paced efforts.